2015
DOI: 10.5296/jsss.v2i2.7213
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Conceptions of Specific Astronomy Concepts: A Longitudinal Investigation

Abstract: The aim of this study is to determine the changes in the knowledge of pre-service Primary and Science teachers related to basic astronomy concepts occurring after four years of undergraduate study in education and the extent of and reasons for these changes. For this purpose, a "Basic Astronomy Test" involving 14 questions was administered to the pre-service Primary and Science teachers by education faculty members in the Black Sea Region of Turkey in the first (2009) determine whether achievement levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(45 reference statements)
0
1
0
6
Order By: Relevance
“…They and Zeilik, Schau, and Mattern (1998) found that preservice teachers scored roughly the same as the school students they were destined to instruct in their future inservice careers. There seems to be a cycle of misconception being passed on through the generations (Ojala 1997;Türk, Sener, and Kalkan 2015). Atwood and Atwood (1996) and Frede (2006) reported prevalent misconceptions among preservice elementary school teachers, whilst Mant and Summers (1993) found that only 4 out of 20 inservice teachers held scientifically valid mental models of the Earth's movement in space.…”
Section: Introductionmentioning
confidence: 99%
“…They and Zeilik, Schau, and Mattern (1998) found that preservice teachers scored roughly the same as the school students they were destined to instruct in their future inservice careers. There seems to be a cycle of misconception being passed on through the generations (Ojala 1997;Türk, Sener, and Kalkan 2015). Atwood and Atwood (1996) and Frede (2006) reported prevalent misconceptions among preservice elementary school teachers, whilst Mant and Summers (1993) found that only 4 out of 20 inservice teachers held scientifically valid mental models of the Earth's movement in space.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, como señala Justi (2006), la construcción de modelos es una actividad con potencial para implicar al alumnado en "hacer ciencia", "pensar sobre ciencia" y "desarrollar pensamiento científico y crítico", algo necesario en la formación de los futuros docentes. Además, se ha demostrado que si los diversos fenómenos astronómicos se aprenden de manera adecuada, las habilidades de comprensión y percepción de los estudiantes se incrementan notablemente, facilitando la comprensión de otros conceptos abstractos en la educación científica (Türk et al 2015).…”
unclassified
“…Esta dificultad se acentúa en básica primaria ya que como es señalado por los trabajos de Appleton (2003) y , los colectivos de maestros de estos niveles, no poseen conocimientos en ciencias, aspecto que refuerza esta problemática. Ahora bien, los conocimientos erróneos sobre algunos fenómenos astronómicos cotidianos terminan siendo heredados a los estudiantes (De De Paor, Dordevic, Karabinos, & Coba, (2017); Turk, Şener, & Kalkan, 2015). Lo que genera que los alumnos de licenciaturas u otras carreras lleguen a las universidades con ideas intuitivas, en su mayoría distanciadas de las concepciones científicas, que incluso se mantienen a lo largo de su formación (Turk, Şener, & Kalkan, 2015).…”
Section: Introductionunclassified
“…Ahora bien, los conocimientos erróneos sobre algunos fenómenos astronómicos cotidianos terminan siendo heredados a los estudiantes (De De Paor, Dordevic, Karabinos, & Coba, (2017); Turk, Şener, & Kalkan, 2015). Lo que genera que los alumnos de licenciaturas u otras carreras lleguen a las universidades con ideas intuitivas, en su mayoría distanciadas de las concepciones científicas, que incluso se mantienen a lo largo de su formación (Turk, Şener, & Kalkan, 2015). Esto es preocupante si se toma en consideración que muchos de estos futuros profesionales serán licenciados, y a futuro estarán a cargo de la enseñanza de algunos conceptos propios de la astronomía en las aulas de clase, propiciando así un círculo vicioso.…”
Section: Introductionunclassified